Hematology journals do not sufficiently adhere to reporting guidelines: a systematic review. (27th February 2017) - Wayant, C.; Smith, C.; Sims, M.; Vassar, M.
Abstract : Essentials Reporting guidelines and trial/review registration aim to limit bias in research. We systematically reviewed hematology journals to examine the use of these policies. Forty‐eight percent of journals made no use of these policies. Improving the use of reporting guidelines will improve research for all stakeholders. Summary: Background: Reporting guidelines and trial/review registration policies have been instituted in order to minimize bias and improve research practices. Objective: The objective of this study was to investigate the policies of hematology journals concerning reporting guideline adoption and trial/review registration. Methods: We performed a web‐based data abstraction from the Instructions for Authors of 67 hematology journals catalogued in the Expanded Science Citation Index of the 2014 Journal Citation Reports to identify whether each journal required, recommended or made no mention of the following reporting guidelines: EQUATOR, ICMJE, CONSORT, MOOSE, QUOROM, PRISMA, STARD, STROBE, ARRIVE and CARE. We also extracted whether journals required or recommended trial or systematic review registration. We e‐mailed editors three times to determine which types of studies their journal accepts. Results: Forty‐eight per cent (32/67) of hematology journals do not adhere to any reporting guidelines. For responding journals, the QUOROM statement, MOOSE, CARE and PROSPERO were the least often mentioned, whereas the ICMJE guidelines, CONSORT statement and general trial registration were most often mentioned. Discussion: Reporting guidelines are infrequently required or recommended by hematology journals. Furthermore, few require clinical trial or systematic review database registration. A higher rate of adherence to reporting guidelines can prevent bias from entering the literature. Participation from all stakeholders, including authors and journal editors, to improve reporting guideline and policy practices is required.